PENGEMBANGAN KURIKULUM PENDIDIKAN DALAM PERSPEKTIF KURIKULUM HUMANISTIK (Studi Kasus di Sekolah Dasar Muhammadiyah Karangbendo Bantul) - MISWANTO, REKA (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2015)
Curriculum is all experience planned by the school to assist students in achieving the learning outcomes to the ability of most excellent students. the curriculum has a very vital role to realize the goal of education in creating a generation that is useful for the country. Curriculum development has many parties involved in this case because it is so large role in education. in the perspective of humanistic curriculum there are several criteria are used as guidelines to develop the curriculum such as: integralistic. the role of the teacher is not authoritative. cooperative learning and evaluation that has no achievement criteria